Discourse quality and discursive context of scientific production in info-comunicative careers at UCLV (Islas, 2022)
Introduction: The present paper characterizes scientific production with a linguistic approach to the careers of Journalism, Social Communication and Information Sciences of the Universidad Central «Marta Abreu» de Las Villas.Methods: Bibliographic-documentary and Discourse Analysis methods as well as the semi-structured interview.Results: Scientific production (especially of Social Communication and Information Sciences) shows a considerable disarticulation in the sequence research problem-conceptual and operational definitions-methods, which results in achievement of limited and superficial results.Conclusions: Finally, it is recommended to promote the academic and scientific exchange of the three degree courses; so that, on the basis of their particular strengths, they contribute to pillate the weaknesses that they respective undergraduate scientific productions have.
Keywords: discourse quality; discursive context; scientific production in communication; linguistic approach